The Sage handbook of criminological research methods - Gadd, David; Karstedt, Susanne; Messner, Steven F. (Sage Publications, 2012)
The SAGE Handbook of Criminological Research Methods focuses on the application of "methods," broadly understood, to address the core substantive questions that currently motivate contemporary criminological research. It maps a canon of methods that are more elaborated than in most other fields of social science, and the intellectual terrain of research problems with which criminologists are routinely confronted. Drawing on exemplary studies, chapters in each section will illustrate the qualitative and quantitative techniques that are commonly applied in empirical studies, as well as the logic of criminological enquiry.